Artificial Intelligence Paradigm in Islamic Education: Epistemological Offerings to the Concept of Teacher and Student - Diana Durrotul Lum'ah; Nasrullah Nasrullah (CV. Intake Pustaka, 2026)
Artificial Intelligence (AI) has brought significant changes to the world of education, including in the realm of Islamic education. This article aims to conceptually and epistemologically examine how the presence of AI influences the structure of the relationship between teachers and students in Islamic education, and how Islamic education can respond critically and constructively to this development. This research uses a literature review method with a qualitative-philosophical approach, primarily based on Islamic epistemology and critiques of modern educational technology. The results of the study indicate that AI shifts the teacher's position from a spiritual guide to a technical facilitator, and positions students as data objects rather than relational subjects. In the context of Islamic education, this shift carries the risk of dehumanization and a reduction in the meaning of knowledge. Therefore, this article offers a framework for Islamic education that is adaptive to AI, which includes the ethics of technology use, repositioning the roles of teachers and students, and strengthening spiritual values in the learning process. The main conclusion of this article emphasizes that Islamic education must position AI as a tool ( wasīlah ) guided by the values of adab and spirituality, rather than as an epistemic authority in the educational process.